An investigation of the relationship between technological and pedagogical content knowledge levels and self-efficacy beliefs of special education teacher candidates - KARAASLAN, ÖZCAN (My University, 2022)
The aim of this study is to examine the relationship between special education teacher candidates' self-efficacy beliefs and their technological pedagogical content knowledge levels. In this study, in which descriptive and relational research design was used, the participant group consisted of 446 special education teacher candidates from three universities. The Teacher Self-Efficacy Belief Scale (SSPS) and the Technological Pedagogical Content Knowledge Scale (TPACKS) were used to collect the data. The collected data were analyzed with the SPSS package program and using parametric tests. It has been observed that the academic competence dimension, which is one of the sub-dimensions of special education teacher candidates, differs significantly according to the age and class variables, and the vocational competence dimension differs significantly according to the gender variable. It was understood that the TPACK scores differed in favor of the older age and class according to the age and class variables. It has been reported that there is a positive and significant relationship between SAS scores and TPACK scores, and that TPACK mean scores explain 18% of self-efficacy beliefs. It has been concluded that as the education level and life experience of the special education teacher candidates are above the average, both self-efficacy belief and technology knowledge increase.
Keywords: Self-Efficacy Beliefs; Special Education Teacher Candidates; The technological and Pedagogical Content Knowledge; Teacher Training